A kind of A-site high entropy perovskite RCoO3 cathode material and preparation method
Preparation of A-position high-entropy perovskite RCoO3 cathode material through traditional solid phase reaction method, solving the problems of complex and high cost of high entropy ceramic preparation process, realizing the preparation of porous structure cathode materials, with good conductivity, and suitable for solids Oxide fuel cell.
Patent Information
- Application Number
- CN202210980753.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as complex preparation process, high cost and low yield when preparing high-entropy ceramics, which limits its wide application.
The traditional solid phase reaction method is used to prepare the A-position high-entropy perovskite RCoO3 cathode material, and is prepared by precise weighing, mixing, ball milling, drying, tableting, pre-firing, grinding, drying, tableting and sintering. Porous structure cathode material of single solid solution.
The obtained A-position high entropy perovskite RCoO3 cathode material has good ion and electron transport channels, which is manifested as metal conductivity, and its resistivity is less than 2.25 (mΩ·cm) in the medium and high temperature range, satisfying the solid oxide fuel cell. Use requirements.
Smart Images

Figure CN115224292B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid oxide fuel cell cathode ceramic materials, and in particular to an A-site high entropy perovskite RCoO3 cathode material and a preparation method thereof. Background Art
[0002] Perovskite oxides have a unique crystal structure, especially after being modified by doping, they have excellent performance and can be used as cathode materials for solid oxide fuel cells, redox catalysts, solar cells, and energy storage materials, etc. They are currently a hot research topic in the field of functional materials. Perovskite-type (ABO3 structure) oxides have abnormal valence states of metal elements, non-stoichiometric ratios of corresponding coordinated oxygen, or different sizes of cation radii in different arrangements and combinations of A and B cations, which cause changes in the tolerance factor t, produce lattice distortion, reduce structural symmetry, and give them special physical and chemical properties.
[0003] The concept of high entropy alloy was independently proposed by Taiwan scholar Ye Junwei, Cantor of Oxford University, and Indian researcher Ranganathan. At present, the concept of high entropy is very popular in the theoretical design of new materials. Its high entropy effect in thermodynamics, relaxation diffusion effect in kinetics, lattice distortion effect in structure, and "cocktail" effect in performance show many excellent properties that cannot be matched by traditional materials. With the continuous deepening of research, Rost et al. successfully introduced the concept of high entropy into oxide ceramic materials in 2015, and successfully developed a single-phase high entropy ceramic composed of 5 different metal ions, which opened up a new path for other complex multi-component oxide ceramics. Compared with traditional ceramic materials, high entropy ceramics have good structural stability, excellent mechanical properties and excellent electromagnetic properties, and have potential applications in the field of new energy materials and medium and high temperature functional materials.
[0004] At present, the new methods for preparing high-entropy ceramics mainly include hot pressing sintering, flash sintering, spark plasma sintering, and spray pyrolysis. These technical means have many problems such as complex preparation process, high cost and low yield, which limit their wide application. The traditional solid phase reaction method is used to prepare high-entropy ceramics, which has the advantages of simple preparation process, high yield, low cost and high repeatability, and has good crystal quality and no secondary phase, which is suitable for wide production and application.
[0005] Perovskite oxides with good ion and electron transport properties, porous structures and good electrochemical catalytic performance are ideal material systems for solid fuel cell (SOFC) cathode materials. There are few reports on A-site high entropy perovskite cathode materials. Summary of the invention
[0006] The purpose of the present invention is to address the problems existing in the background technology and to propose an A-site high entropy perovskite RCoO3 cathode material.
[0007] The technical solution of the present invention is: an A-site high entropy perovskite RCoO3 cathode material, the chemical formula of the A-site high entropy perovskite RCoO3 cathode material is (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3.
[0008] A method for preparing an A-site high entropy perovskite RCoO3 cathode material specifically comprises the following steps:
[0009] S1. Weighing;
[0010] According to the chemical formula (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) The stoichiometric ratio of La, Sr, Ba, Ca and Nd in CoO3 is accurately weighed as raw materials La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4; wherein, in molar ratio, La:Sr:Ba:Ca:Nd:Co=0.2:0.2:0.2:0.2:0.2:1;
[0011] S2, mixed;
[0012] Weighed La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4 were placed in a ball mill, and ball milling media was added, and the mixture was ball milled for 11 to 13 hours to obtain a mixture A;
[0013] S3, drying;
[0014] The mixture A is baked at 100-120° C. in an air atmosphere for 11-13 hours to obtain a precursor powder B;
[0015] S4, tableting;
[0016] Precursor powder B was first manually ground in a mortar for 12 to 18 minutes before tableting;
[0017] The tableting conditions are as follows: the tableting pressure is increased from 0 MPa to 5 MPa, maintained for 3 to 7 minutes, and then increased to 6 MPa, maintained for another 3 to 7 minutes, to obtain a sheet block C;
[0018] S5, pre-burning;
[0019] Pre-calcining the sheet block C at 900-920°C in air atmosphere for 23-25h to obtain block D;
[0020] S6, secondary grinding;
[0021] The block D was crushed and ball-milled again for 11 to 13 hours to obtain powder E;
[0022] S7, secondary drying;
[0023] The obtained powder E is dried in an air atmosphere at 100-120° C. for 11-13 hours to obtain powder F;
[0024] S8, secondary tableting;
[0025] Powder F was manually ground in a mortar for 12 to 18 minutes before tableting;
[0026] The tableting conditions are as follows: the tableting pressure increases from 0 MPa to 8-10 MPa, and the pressure is maintained for 2-5 minutes for each increase of 1-2 MPa, to obtain a sheet block G;
[0027] S9, sintering;
[0028] The sheet block material G is placed in a muffle furnace, the temperature is raised to 1000-1200° C. in an air atmosphere, and the sintering time is 20-24 hours to obtain an A-site high entropy perovskite RCoO3 cathode material.
[0029] Preferably, the ball milling medium in S2 is anhydrous ethanol, and the grinding balls used for ball milling are zirconia balls. The total mass of La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4, the total mass of zirconia balls and the total mass of anhydrous ethanol are 1:5:5.
[0030] Preferably, in S5, the sheet block material C is pre-sintered at a heating rate of 10°C / min.
[0031] Preferably, the tableting pressure in S8 is 10 MPa, and the pressure is maintained for 5 minutes every time the pressure increases by 2 MPa.
[0032] Preferably, the size of the sheet block G in S8 is φ20mm*3mm or 13mm*5mm*4mm.
[0033] Preferably, the flaky block material G in S9 is heated to 1100° C. at a heating rate of 5° C. / min and kept at that temperature for 24 hours, then cooled to 600° C. at a cooling rate of 5° C. / min and then cooled in the furnace.
[0034] Compared with the prior art, the above technical solution of the present invention has the following beneficial technical effects:
[0035] The A-site high entropy perovskite RCoO3 cathode material prepared by the present invention is a single solid solution, which is a porous structure and has good ion and electron transmission channels, meeting the ion and electron exchange requirements of the cathode material; the prepared (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )The resistivity of CoO3 cathode material increases with the increase of temperature, showing a kind of metallic conductive behavior. The resistivity in the medium and high temperature range is lower than 2.25 (mΩ·cm), which can better meet the use requirements of solid oxide fuel cells (SOFC). It can also fine-tune the component ratio and modulate its physical and chemical properties to better meet the actual needs of solid oxide fuel cell cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 for (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )XRD spectrum of CoO3 cathode material.
[0037] Figure 2 for (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )Scanning electron microscope image of the cross-sectional microstructure and element distribution of CoO3 cathode material.
[0038] Figure 3 Schematic diagram of resistance measurement using the DC four-probe method.
[0039] Figure 4 for (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) Measured resistivity versus temperature curve of CoO3 cathode material. DETAILED DESCRIPTION
[0040] Embodiment 1
[0041] The present invention proposes an A-site high entropy perovskite RCoO3 cathode material, including the A-site high entropy perovskite RCoO3 cathode material having a chemical formula of (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3.
[0042] Embodiment 2
[0043] A method for preparing an A-site high entropy perovskite RCoO3 cathode material specifically comprises the following steps:
[0044] S1. Weighing;
[0045] According to the chemical formula (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) The stoichiometric ratio of La, Sr, Ba, Ca and Nd in CoO3 is accurately weighed as raw materials La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4; wherein, in molar ratio, La:Sr:Ba:Ca:Nd:Co=0.2:0.2:0.2:0.2:0.2:1;
[0046] S2, mixed;
[0047] Weighed La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4 were placed in a ball mill, and ball milling media was added, and the mixture was ball milled for 11 to 13 hours to obtain a mixture A;
[0048] The ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls, and the total mass of La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4, the total mass of zirconia balls and the total mass of anhydrous ethanol is 1:5:5;
[0049] S3, drying;
[0050] Place the mixture A in an oven and bake it at 100°C in air atmosphere for 11 hours to obtain precursor powder B;
[0051] S4, tableting;
[0052] Precursor powder B was manually ground in a mortar for 12 min before tableting;
[0053] The tableting conditions are as follows: the tableting pressure is increased from 0 MPa to 5 MPa, maintained for 3 minutes, and then increased to 6 MPa, maintained for another 3 minutes, to obtain a sheet block C;
[0054] Further, the uniformly mixed fine powder was pressed into a sheet-like embryo using a φ20 mm die, and the tableting conditions were 5 MPa / 5 min+6 MPa / 5 min;
[0055] S5, pre-burning;
[0056] The sheet block C was pre-sintered at 900°C in an air atmosphere for 23 hours to obtain a block D; wherein the sheet block C was pre-sintered at a heating rate of 10°C / min until the temperature reached 900°C;
[0057] S6, secondary grinding;
[0058] The block D was crushed and ball-milled again for 11 hours to obtain powder E; the ball-milling conditions in S6 were in cylinder S2;
[0059] S7, secondary drying;
[0060] The obtained powder E was dried in an air atmosphere at 100°C for 11 hours to obtain powder F;
[0061] S8, secondary tableting;
[0062] Powder F was put into a mortar and ground manually for 12 minutes before tableting; the pressure during tableting was 10 MPa, and the pressure was maintained for 5 minutes for each increase of 2 MPa;
[0063] The tableting conditions are as follows: the tableting pressure increases from 0 MPa to 8 MPa, and the pressure is maintained for 2 minutes for each increase of 1 MPa, to obtain a sheet block G; the size of the sheet block G is φ20 mm*3 mm or 13 mm*5 mm*4 mm;
[0064] S9, sintering;
[0065] The sheet block G was placed in a muffle furnace, and the temperature was raised to 1000°C in an air atmosphere, and the sintering time was 20 hours to obtain the A-site high entropy perovskite RCoO3 cathode material;
[0066] Among them, the sheet block G in S9 was heated to 1000°C at a heating rate of 5°C / min and kept at that temperature for 20h, then cooled to 600°C at a cooling rate of 5°C / min and then cooled in the furnace; when the temperature dropped to 600°C, it was kept at that temperature for 30min, and the sintering atmosphere was air.
[0067] Embodiment 3
[0068] A method for preparing an A-site high entropy perovskite RCoO3 cathode material specifically comprises the following steps:
[0069] S1. Weighing;
[0070] According to the chemical formula (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2) The stoichiometric ratio of La, Sr, Ba, Ca and Nd in CoO3 is accurately weighed as raw materials La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4; wherein, in molar ratio, La:Sr:Ba:Ca:Nd:Co=0.2:0.2:0.2:0.2:0.2:1;
[0071] S2, mixed;
[0072] Weighed La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4 were placed in a ball mill, ball milling media was added, and ball milling was performed for 12 hours to obtain a mixture A;
[0073] The ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls, and the total mass of La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4, the total mass of zirconia balls and the total mass of anhydrous ethanol is 1:5:5;
[0074] S3, drying;
[0075] The mixture A was placed in an oven and dried at 110°C in an air atmosphere for 12 hours to obtain a precursor powder B;
[0076] S4, tableting;
[0077] Precursor powder B was manually ground in a mortar for 15 min before tableting;
[0078] The tableting conditions are as follows: the tableting pressure is increased from 0 MPa to 5 MPa, maintained for 5 minutes, and then increased to 6 MPa, maintained for another 5 minutes, to obtain a sheet block C;
[0079] Further, the uniformly mixed fine powder was pressed into a sheet-like embryo using a φ20 mm die, and the tableting conditions were 5 MPa / 5 min+6 MPa / 5 min;
[0080] S5, pre-burning;
[0081] The sheet block C is pre-sintered at 910°C in an air atmosphere for 24 hours to obtain a block D; wherein the sheet block C is pre-sintered at a heating rate of 10°C / min until the temperature reaches 910°C;
[0082] S6, secondary grinding;
[0083] The block D was crushed and ball-milled again for 12 hours to obtain powder E; the ball-milling conditions in S6 were in cylinder S2;
[0084] S7, secondary drying;
[0085] The obtained powder E was dried at 110°C in air atmosphere for 12 hours to obtain powder F;
[0086] S8, secondary tableting;
[0087] Powder F was put into a mortar and ground manually for 15 minutes before tableting; the pressure during tableting was 10MPa, and the pressure was maintained for 5 minutes for each 2MPa increase;
[0088] The tableting conditions are as follows: the tableting pressure increases from 0 MPa to 9 MPa, and the pressure is maintained for 3 minutes every time the pressure increases by 1.5 MPa, to obtain a sheet block G; the size of the sheet block G is φ20 mm*3 mm or 13 mm*5 mm*4 mm;
[0089] S9, sintering;
[0090] The sheet block G was placed in a muffle furnace, and the temperature was raised to 1100°C in an air atmosphere, and the sintering time was 22 hours to obtain the A-site high entropy perovskite RCoO3 cathode material;
[0091] Among them, the sheet block G in S9 was heated to 1100°C at a heating rate of 5°C / min and kept at that temperature for 22h, then cooled to 600°C at a cooling rate of 5°C / min and then cooled in the furnace; when the temperature dropped to 600°C, it was kept at that temperature for 30min, and the sintering atmosphere was air.
[0092] Embodiment 4
[0093] A method for preparing an A-site high entropy perovskite RCoO3 cathode material specifically comprises the following steps:
[0094] S1. Weighing;
[0095] According to the chemical formula (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) The stoichiometric ratio of La, Sr, Ba, Ca and Nd in CoO3 is accurately weighed as raw materials La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4; wherein, in molar ratio, La:Sr:Ba:Ca:Nd:Co=0.2:0.2:0.2:0.2:0.2:1;
[0096] S2, mixed;
[0097] Weighed La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4 were placed in a ball mill, and ball milling media was added, and the mixture was ball milled for 11 to 13 hours to obtain a mixture A;
[0098] The ball milling medium is anhydrous ethanol, the grinding balls are zirconia balls, and the total mass of La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4, the total mass of zirconia balls and the total mass of anhydrous ethanol is 1:5:5;
[0099] S3, drying;
[0100] The mixture A was placed in an oven and dried at 120°C in an air atmosphere for 13 hours to obtain a precursor powder B;
[0101] S4, tableting;
[0102] Precursor powder B was manually ground in a mortar for 18 min before tableting;
[0103] The tableting conditions are as follows: the tableting pressure is increased from 0 MPa to 5 MPa, maintained for 7 minutes, and then increased to 6 MPa, maintained for another 7 minutes, to obtain a sheet block C;
[0104] Further, the uniformly mixed fine powder was pressed into a sheet-like embryo using a φ20 mm die, and the tableting conditions were 5 MPa / 5 min+6 MPa / 5 min;
[0105] S5, pre-burning;
[0106] The sheet block C is pre-sintered at 920°C in an air atmosphere for 25 hours to obtain a block D; wherein the sheet block C is pre-sintered at a heating rate of 10°C / min until the temperature reaches 920°C;
[0107] S6, secondary grinding;
[0108] The block D was crushed and ball-milled again for 13 h to obtain powder E; the ball-milling conditions in S6 were in cylinder S2;
[0109] S7, secondary drying;
[0110] The obtained powder E was dried at 120°C in air atmosphere for 13 hours to obtain powder F;
[0111] S8, secondary tableting;
[0112] Powder F was manually ground in a mortar for 18 minutes and then tableted; the pressure during tableting was 10 MPa, and the pressure was maintained for 5 minutes for each 2 MPa increase;
[0113] The tableting conditions are as follows: the tableting pressure increases from 0 MPa to 10 MPa, and the pressure is maintained for 5 minutes for each increase of 2 MPa, to obtain a sheet block G; the size of the sheet block G is φ20 mm*3 mm or 13 mm*5 mm*4 mm;
[0114] S9, sintering;
[0115] The sheet block G was placed in a muffle furnace, and the temperature was raised to 1200°C in an air atmosphere, and the sintering time was 24 hours to obtain the A-site high entropy perovskite RCoO3 cathode material;
[0116] Among them, the sheet block G in S9 was heated to 1200°C at a heating rate of 5°C / min and kept at that temperature for 24h, then cooled to 600°C at a cooling rate of 5°C / min and then cooled in the furnace; when the temperature dropped to 600°C, it was kept at that temperature for 30min, and the sintering atmosphere was air.
[0117] Example 2-4 obtained (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )Performance of CoO3 cathode material:
[0118] 1. (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )Phase structure characterization of CoO3 cathode material
[0119] X-ray diffraction was used to determine the phase structure of the A-site high entropy perovskite RCoO3 cathode material, such as Figure 1 As shown, it is the prepared A-site high entropy perovskite (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) XRD spectrum of CoO3 cathode material, from Figure 1 It can be seen that (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) The CoO3 cathode material has strong diffraction peaks at 33.02, 40.74, 47.38 and 58.96, which are consistent with the diffraction peaks of the cubic phase (PDF#48-0137) in the standard PDF card, and the space group is And there is no second phase and split peak, which can be confirmed that the A-site high entropy perovskite (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3 cathode material is a single solid solution.
[0120] 2. (La 0.2 Sr 0.2 Ba 0.2 Ca0.2 Nd 0.2 )Cross-sectional microstructure and element distribution of CoO3 cathode material
[0121] A tungsten filament scanning electron microscope (with energy dispersive spectrometer) was used to observe the A-site high entropy perovskite (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) Cross-sectional morphology of CoO3 cathode material, from Figure 2 It can be seen that the A-site high entropy perovskite (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3 cathode material has a porous structure, which is conducive to ion and electron exchange, suitable for the needs of cathode materials, and the elements are evenly distributed without individual element aggregation, which further proves that (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3 cathode material is a single solid solution.
[0122] 3. (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )Resistivity test of CoO3 cathode material
[0123] The DC four-probe method was used to test (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )The resistance value of CoO3 cathode material is 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) CoO3 cathode material resistance test, the test temperature range is 30 ~ 700 ℃. The DC four-probe method resistance measurement schematic diagram is as follows Figure 3 As shown:
[0124] The resistivity calculation formula is: ρ = (R*S) / L; where ρ is the resistivity of the cathode material, R is the resistance of the cathode material, S is the cross-sectional area of the strip sample, and L is the length of the strip sample.
[0125] Figure 4 for (La 0.2 Sr0.2 Ba 0.2 Ca 0.2 Nd 0.2 )The resistivity and temperature curve of CoO3 cathode material measured, from Figure 4 It can be seen that (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )The resistivity of CoO3 cathode material increases with the temperature, showing a metallic conductive behavior; in the temperature window of 30-700℃, the resistivity of cathode material is lower than 2.25 (mΩ·cm), which can better meet the application requirements of solid oxide fuel cells (SOFC).
[0126] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing an A-site high entropy perovskite RCoO3 cathode material, characterized in that: The chemical formula of the A-site high entropy perovskite RCoO3 cathode material is (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 )CoO3; The preparation method specifically comprises the following steps: S1. Weighing; According to the chemical formula (La 0.2 Sr 0.2 Ba 0.2 Ca 0.2 Nd 0.2 ) The stoichiometric ratio of La, Sr, Ba, Ca and Nd in CoO3 is accurately weighed as raw materials La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4; wherein, in molar ratio, La:Sr:Ba:Ca:Nd:Co=0.2:0.2:0.2:0.2:0.2:1; S2, mixed; Weighed La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4 were placed in a ball mill, and ball milling media was added, and the mixture was ball milled for 11 to 13 hours to obtain a mixture A; S3, drying; The mixture A is baked at 100-120° C. in an air atmosphere for 11-13 hours to obtain a precursor powder B; S4, tableting; Precursor powder B was first manually ground in a mortar for 12 to 18 minutes before tableting; The tableting conditions are as follows: the tableting pressure is increased from 0 MPa to 5 MPa, maintained for 3 to 7 minutes, and then increased to 6 MPa, maintained for another 3 to 7 minutes, to obtain a sheet block C; S5, pre-burning; Pre-calcining the sheet block C at 900-920°C in air atmosphere for 23-25h to obtain block D; S6, secondary grinding; The block D was crushed and ball-milled again for 11 to 13 hours to obtain powder E; S7, secondary drying; The obtained powder E is dried in an air atmosphere at 100-120° C. for 11-13 hours to obtain powder F; S8, secondary tableting; Powder F was manually ground in a mortar for 12 to 18 minutes before tableting; The tableting conditions are as follows: the tableting pressure increases from 0 MPa to 8-10 MPa, and the pressure is maintained for 2-5 minutes for each increase of 1-2 MPa, to obtain a sheet block G; S9, sintering; The sheet block G is placed in a muffle furnace, the temperature is raised to 1200°C in an air atmosphere, and the sintering time is 20 to 24 hours to obtain an A-site high entropy perovskite RCoO3 cathode material whose resistivity increases with increasing temperature.
2. The method for preparing an A-site high entropy perovskite RCoO3 cathode material according to claim 1, characterized in that: In S2, anhydrous ethanol is used as the ball milling medium, and zirconia balls are used as the grinding balls for ball milling. The total mass of La2O3, CaCO3, SrCO3, BaCO3, Nd2O3 and Co3O4, the total mass of zirconia balls and the total mass of anhydrous ethanol are 1:5:
5.
3. The method for preparing an A-site high entropy perovskite RCoO3 cathode material according to claim 1, characterized in that: In S5, the sheet block C is pre-sintered at a heating rate of 10°C / min.
4. The method for preparing an A-site high entropy perovskite RCoO3 cathode material according to claim 1, characterized in that: The tableting pressure in S8 is 10 MPa, and the pressure is maintained for 5 minutes every time the pressure increases by 2 MPa.
5. The method for preparing an A-site high entropy perovskite RCoO3 cathode material according to claim 1, characterized in that: The size of the sheet block G in S8 is φ20mm*3mm or 13mm*5mm*4mm.
6. The method for preparing an A-site high entropy perovskite RCoO3 cathode material according to claim 1, characterized in that: The flaky block material G in S9 was heated to 1100°C at a heating rate of 5°C / min and kept at that temperature for 24h, then cooled to 600°C at a cooling rate of 5°C / min and then cooled in the furnace.
Citation Information
Patent Citations
A-site high-entropy perovskite ReMnO3 thermoelectric ceramic and preparation method thereof
CN114133215A
Cathode for solid oxide fuel cells and electrolysis cells, method for fabricating the same
KR1020120127848A